1999
DOI: 10.1128/iai.67.1.294-301.1999
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio anguillarumResistance to Rainbow Trout (Oncorhynchus mykiss) Serum: Role of O-Antigen Structure of Lipopolysaccharide

Abstract: The sensitivity of Vibrio anguillarum to the bactericidal effect of rainbow trout serum was investigated with different strains of serogroups O1 and O2a, which are the most frequently found serogroups in clinical outbreaks of vibriosis. All of the V. anguillarum strains were able to activate complement in rainbow trout serum, but smooth strains of V. anguillarum serogroup O1 were resistant to complement-mediated killing in the absence of specific antibodies. In the case of V. anguillarum serogroup O2a strains,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…Although bt 2 isolates possessed a different overall structure, no correlation in virulence could be established. Of relevance, it has been demonstrated by Boesen et al (1999) that virulent isolates of Vibrio anguillarum, which possessed a smooth LPS structure, were resistant to serum killing. However, unlike mammals, fish appear to be immune to the septic shock effects of LPS (MacKenzie et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although bt 2 isolates possessed a different overall structure, no correlation in virulence could be established. Of relevance, it has been demonstrated by Boesen et al (1999) that virulent isolates of Vibrio anguillarum, which possessed a smooth LPS structure, were resistant to serum killing. However, unlike mammals, fish appear to be immune to the septic shock effects of LPS (MacKenzie et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that both virulent and non-virulent F. psychrophilum were resistant to the action of the complement activity present in the rainbow trout serum. Whether this serum resistance is mediated by the presence of LPS and a polysaccharide capsule, as has been demonstrated for other fish pathogens Boesen et al 1999), remains to be elucidated.…”
Section: Interaction Of F Psychrophilum With the Fish Immune Systemmentioning
confidence: 91%
“…Vibriosis causes a high mortality in infected fish and is responsible for great losses in aquaculture (Egiduis, 1987). The diverse products secreted by V. anguillarum have been reported as being associated with its pathogenesis, such as the iron-uptake system (Crosa, 1980), hemolysin (Kodama et al, 1984), lipopolysaccharide (LPS) (Norqvist & Wolf-Watxtz, 1993;Boesen et al, 1999) and cytotoxin (Kodama et al, 1985). In addition, the extracellular zinc metolloprotease, EmpA, was also identified as an important factor in virulence, as it helps bacterial pathogens to enter host cells (Inamura et al, 1985;Norqvist et al, 1990;Farrell & Crosa, 1991).…”
Section: Introductionmentioning
confidence: 99%